Structure-based design of antiviral drug candidates targeting the SARS-CoV-2 main protease - Dai, Wenhao; Zhang, Bing; Jiang, Xia-Ming; Su, Haixia; Li, Jian; Zhao, Yao; Xie, Xiong; Jin, Zhenming; Peng, Jingjing; Liu, Fengjiang; Li, Chunpu; Li, You; et al. (Science (American Association for the Advancement of Science), 2020)
With no vaccine or proven effective drug against the virus that causes coronavirus disease 2019 (COVID-19), scientists are racing to find clinical antiviral treatments. A promising drug target is the viral main protease M pro , which plays a key role in viral replication and transcription. Dai et al. designed two inhibitors, 11a and 11b, based on analyzing the structure of the M pro active site. Both strongly inhibited the activity of M pro and showed good antiviral activity in cell culture. Compound 11a had better pharmacokinetic properties and low toxicity when tested in mice and dogs, suggesting that this compound is a promising drug candidate. Science , this issue p. 1331 Two peptidomimetic aldehydes were designed, synthesized, and evaluated as antiviral drug candidates. SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) is the etiological agent responsible for the global COVID-19 (coronavirus disease 2019) outbreak. The main protease of SARS-CoV-2, M pro , is a key enzyme that plays a pivotal role in mediating viral replication and transcription. We designed and synthesized two lead compounds ( 11a and 11b ) targeting M pro . Both exhibited excellent inhibitory activity and potent anti–SARS-CoV-2 infection activity. The x-ray crystal structures of SARS-CoV-2 M pro in complex with 11a or 11b , both determined at a resolution of 1.5 angstroms, showed that the aldehyde groups of 11a and 11b are covalently bound to cysteine 145 of M pro . Both compounds showed good pharmacokinetic properties in vivo, and 11a also exhibited low toxicity, which suggests that these compounds are promising drug candidates.